Successful Surgical Management of Sebaceous Gland Tumours in Dogs - Parmar, JJ; Shah, AI; Rao, Neha; Godasara, DJ; Patel, DM (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Tumors of the skin and subcutaneous tissues are most common in Veterinary practice and account for  approximately one-third of all the tumors in dogs (Chikweto  et al., 2011). Sebaceous hyperplasia is a most common  tumor of the sebaceous gland that occurs in the old age,  anywhere on the body as wart-like or cauliflower-like and  can become ulcerated because of trauma, while sebaceous  epithelioma occurs primarily on the head as a solitary lesion  but generalized cases have been reported. The treatment  of choice is surgical excision (Max’s House, 2005). This paper  presents case studies of sebaceous gland tumors in two dogs.
Keywords: Age; Gir cattle; Haemoprotozoan infection; Prevalence; Season